Prevalence and risk factors associated with postpartum depression among mothers in selected municipalities of Bardiya, Nepal - Paudel, Sandesh; Lamichhane, Nabin; Kumari Paudel, Binita; Gautam, Jamuna; Ram Magar, Babu; Kandel, Suresh; Adhikari, Samarpan (Journal of Chitwan Medical College, 2024)
Background: Depression is a prevalent mental health condition characterized by enduring sadness and reduced interest in activities. Postpartum depression is a significant issue, impacting 10-15% of women post-childbirth, affecting both mothers and families. This study aimed to assess the prevalence and risk factors associated with postpartum depression among mothers in Bardiya, Nepal. Method: A community-based cross-sectional study was conducted among 164 mothers in the postnatal period in Bardiya, Nepal. The Edinburgh Postpartum Depression Scale, with a cut-off value of ≥12, was utilized to assess depressive syndrome. Chi-square and logistic regression analyses were used to determine associations with postpartum depression and related factors. Result: The prevalence of depressive symptoms among postpartum mothers was 29.4%. In bivariate analysis, family income, drinking and smoking habits of both respondents and husband, child being hospitalized, husband's occupation, conflicts with family members, and obstetric history were significantly associated with postpartum depression (p<0.05). In multivariate logistic regression, family monthly income <30,000 (AOR=4.90, 95% CI: 1.13-21.15), multiparity (AOR=10.42, 95% CI: 1.68-64.51) and complications after delivery (AOR=10.21, 95% CI: 2.30-45.36) were factors significantly associated with postpartum depressive symptoms. Conclusion: Almost one-third of the respondents experienced postpartum depressive symptoms. Family monthly income, parity, and complication after delivery were found to be associated with postpartum depression. The findings emphasize the importance of regular screening at health posts and primary healthcare centers, facilitating timely referrals for counseling and treatment.